Interspecific interactions in nesting and feeding urban sites among introduced Monk Parakeet (Myiopsitta monachus) and syntopic bird species. Issue 2 (4th March 2017) - Di Santo, Marianna; Battisti, Corrado; Bologna, Marco A.
Abstract : Monk Parakeet ( Myiopsitta monachus ) is a successful invader of many European urbanised habitats. Here, we report evidence of interspecific interactions between this species and some synanthropic co-occurring birds in three urban parks of Rome (central Italy). In both nesting and feeding sites, we recorded 158 interactions with seven syntopic species in eight colonial focal nests (0.74 events/hr). The number and frequency of interactions significantly differ among nests and species, the Italian Sparrow ( Passer italiae ) being the most interactive species. For this species, the frequency of interactions was normally distributed between different months with a peak in June. We also observed a case of nest cohabitation, as well as predatory attacks carried out by Hooded Crow ( Corvus cornix ). As far as foraging sites are concerned, 11 out of 74 clusters of parakeets (15%) hosted four bird species, mainly Starling, Sturnus vulgaris, but we did not observe any interactions. Although Monk Parakeet is a social bird generally tolerant towards other species near their nests and in foraging areas, we observed interspecific interactions in nesting sites as a response to competitive or predatory mechanisms. Italian Sparrows interact because they use parakeet nests as a secondary structure for nesting (cohabitation) and, probably, because of the wide availability of food resources (invertebrates) useful for juvenile recruitment. The interaction of parakeets with Hooded Crow is a response to predatory attacks on eggs or juveniles. However, interspecific interactions seem to be occasional events in nesting sites and are apparently absent in feeding sites, where competitive behaviour is probably reduced due to high availability of plant resources. In urbanised areas, where Monk Parakeets have recently been introduced, the number of competitors and predators might be very reduced (both in number of events and species) in comparison to native areas where competition and predatory mechanisms reflect long-term co-evolutionary dynamics.